The use of botulinum peptide in facial renewal: case report (Research, Society and Development, 2021)
The patient, C.H.B, 33 years old, female, attended the NAEO/SC clinic with the main complaint of: skin cracks, wrinkles, age spots with discoloration and irregularities; looking for facial rejuvenation treatment. After anamnesis and clinical examination, it was decided to use microneedling all over the face, followed by the application of “Professional Dermoline” in a smear. At the end, the “Facial Mask” was made for a period of 40 minutes. The same protocol was repeated twice more, totaling three therapy sessions, with an interval of 30 days between them. Maintenance was carried out at home with the “Anti-wrinkle Serum” throughout the treatment period. Facial skin analysis was performed using the FaceBox Pro® Facial Scanner in which the patient's skin age was 31.23 years. In the digital analysis of the skin performed using the Skin Up ® device, the moisture content was 22.3% and the oil content was 33.4%. After the complete treatment and a new examination, with FaceBox Pro® there was a reduction in age from 31.46 to 30.17 years and with Skin Up® it was not necessary to reassess, as the patient's skin was already close to normal indices. It can be concluded that when botulinum peptide is used properly and with the correct indication, it is possible to obtain significant results in the quality of the patient's skin.